T Cell Activation in South African HIV-Exposed Infants Correlates with Ochratoxin A Exposure - Wood, Lianna Frances; Wood, Matthew P.; Fisher, Bridget S.; Jaspan, Heather B.; Sodora, Donald L. (Frontiers in Immunology, 2017)
The introduction of non-breastmilk foods to HIV-infected infants is associated with increased levels of immune activation, which can impact the rate of HIV disease progression. This is particularly relevant in countries where mother-to-child transmission of HIV still occurs at unacceptable levels. The goal of this study was to evaluate the levels of the toxic food contaminant ochratoxin A (OTA) in HIV-exposed South African infants that are either breastfed or consuming non-breast milk foods. OTA is a common mycotoxin, found in grains and soil, that is toxic at high doses but has immuno-modulatory properties at lower doses. Samples from HIV-exposed and HIV-unexposed infants enrolled in prospective observational cohort studies were collected and analyzed at birth through 14 weeks of age. We observed that infants consuming non-breast milk foods had significantly higher plasma levels of OTA at 6 weeks of age compared to breastfed infants, increasing until 8 weeks of age. The blood levels of OTA detected were comparable to levels observed in OTA-endemic communities. OTA plasma levels correlated with HIV target cell activation, (CCR5 and HLADR expression on CD4+ T cells) and plasma levels of the inflammatory cytokine CXCL10. These findings provide evidence that elevated OTA levels in South African infants are associated with the consumption of non-breastmilk foods and activation of the immune system. Reducing infant OTA exposure has the potential to reduce immune activation and provide health benefits, particularly in those infants that are HIV-exposed or HIV-infected.